Voltammetric DNA Biosensor using Gold Electrode Modified by Self Assembled Monolayer of Thiol for Detection of Mycobacterium Tuberculosis. (2017) - Gaffar, Shabarni; Nurmalasari, Ratna; Yohan,; Hartati, Yeni W.
Abstract: Mycobacterium tuberculosis is an infectious agent that causes tuberculosis (TB). TB is one of the major causes of death worldwide, mainly in the developing country. Early and rapid diagnosis of TB will be of great help to isolate the patients and control the disease. The aim of this research is to detect Mycobacterium tuberculosis using voltammetric DNA biosensor by using gold electrode modified by self assembled monolayer with thiol. Single-stranded probe DNA was immobilized on the surface of self assembled monolayer gold electrode with the assistance of cysteamine and glutaraldehyde, which was further used to hybridize with the target DNA sequence and non-complementary target sequence. Differential Pulse Voltammetry (DPV) was used to study the immobilization of DNA probe and hybridization with the target DNA. The hybridization reaction on the gold electrode surface was detected by monitoring a guanine oxidation signal at +0.2 Volt. Voltammetric DNA biosensor using gold electrode modified with thiol can be used to determine hybridization between probe DNA and target DNA sequence of M. tuberculosis with sensitivity value is 0.5175 for target DNA in concentration range 0- 30 μg/mL; detection limit is 2.7046 μg/mL and quantification limit is 9.0155 μg/mL, accuracy is 99.22%, precision 99.86%